Peran Teknologi ChatGPT dalam Optimalisasi Layanan Referensi bagi Mahasiswa di Perpustakaan Universitas Prima Indonesia - Wahyuni, Nur; Yasmin, Nabila (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The rapid development of information and communication technology provides recommendations for libraries to optimize reference services to remain relevant and effective for users. One of the latest technologies that can be utilized is ChatGPT. ChatGPT is a large language model developed by OpenAI. This research aims to explore the role of ChatGPT technology in optimizing reference services for students at Prima Indonesia University Library. This study also seeks to identify the factors influencing the utilization of ChatGPT technology by students in accessing reference services. This research uses a qualitative approach with a case study method involving in-depth interviews with librarians and students, participatory observation, and document analysis. Thematic analysis will be used to analyze the collected data, ensuring data validity through source triangulation and member checking. This research is expected to provide insights into the potential of ChatGPT in enhancing reference services for students at Prima Indonesia University and offer recommendations for libraries to leverage the latest technology in optimizing their services. ChatGPT plays an important role in optimizing reference services for students at the Prima Indonesia University library. This technology offers easy access to information, search efficiency, and practicality which really helps students in meeting their reference needs.